Comparison of thermophilic Campylobacter spp. occurrence in two types of retail chicken samples - Tang, John Yew Huat; Mohamad Ghazali, Farinazleen; Abdul Aziz, Saleha; Nishibuchi, Mitsuaki; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2009)
The aim of this study is to compare the occurrence of thermophilic Campylobacter spp. in chicken retail at wet markets and hypermarkets. Campylobacter contaminations in chicken samples from wet market (70.7%) were comparatively lower than chicken samples sold in hypermarket (91.4%). Of the 77 Campylobacter isolates, 59 (76.6%) were identified as Campylobacter jejuni and 18 (23.4%) isolates were identified as C. coli. All Campylobacter isolates are multi-resistant to the antimicrobial agents. Most of the isolates were resistant to tetracycline (92.2%) and erythromycin (98.7%). This study concluded that chicken samples from both wet market and hypermarket were contaminated with Campylobacter, most of which are antimicrobial-resistant strains.